Analisis Kelayakan Fasilitas Check-In berdasarkan Pelaksanaan Inspeksi Airport Operation Landside And Terminal di Yogyakarta International Airport - Berliana Nur Fitria Artiwi; Amelia Puspa Tamara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine and analyze the suitability of check-in area facilities based on inspections conducted by the Airport Operation Landside and Terminal (AOLT) Unit, as well as to examine the implementation of check-in area facility inspections at Yogyakarta International Airport. The research method used is a qualitative approach with a descriptive research design. Data collection techniques included observation, interviews, and documentation, with informants consisting of staff involved in operational activities and inspections of terminal area facilities. Research documentation utilized the Daily Logbook of the Airport Operation Landside and Terminal (AOLT) at Yogyakarta International Airport and the Optima Report as supporting data. The research findings indicate that check-in area facilities—including check-in counters, baggage conveyor belts, the Flight Information Display System (FIDS), signage/directional signs, queue lines, and restrooms—are generally available and in adequate condition to support passenger service operations. Based on research indicators—which include facility availability, functional condition of facilities, operational readiness, and compliance with service standards—inspections conducted by the Airport Operation Landside and Terminal (AOLT) Unit play a key role in maintaining facility conditions through inspection activities, identification of findings, documentation of inspection results, and coordination of follow-up actions for facilities requiring attention. The conclusions of this study indicate that the inspections conducted by the Airport Operation Landside and Terminal (AOLT) Unit have supported efforts to maintain the serviceability of the check-in area facilities at Yogyakarta International Airport. However, ongoing monitoring, maintenance, and evaluation remain necessary to ensure that the condition of the facilities and the quality of operational services can be sustained.